Pengaruh Honeycomb Sandwich Terhadap Perilaku Perambatan Retak Lelah Al 2024-T3 Pada Beban Amplitudo Konstan - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Kedokteran Hewan UGM, 2000)
This research investigated the effect of the honeycomb sandwich on the characteristic of fatigue crack growth rate of aluminum alloy Al 2024-T3. The test was carried out under sinusiodal loads with constant amplitude at the stress ratio (R) of 0,3 and 0,6. The experimental results show that the fatigue crack growth rate are retarded when it reached honeycomb side. The effect of the stress ratio can decrease the crack growth rate for higher stress ratio